Interruptions Employed by the Participants of Ellen DeGeneres Show - Fatonah, Astri Amaliah; Sofyan, Dedi; Zahrida, Zahrida (Journal of English Education and Teaching, 2024)
This research aimed to find out the dominant types of interruptions employed by participants and to find out the purposes of interruptions done by the participants of Ellen DeGeneres show. This research employed quantitative descriptive research. The subjects of this research were two of the most viewed videos uploaded from October-November 2020. The interruption employed by the participants and the purposes of interruptions done by the participants were classified using an instrument datasheet following Murata’s theory. The first results of this research show that interruptions types done by the participants of the Ellen DeGeneres show namely cooperative and intrusive, and the dominant types employed in the Ellen DeGeneres show was a cooperative interruption. The second result finding showed all that the purposes of interruptions done by the participants of the Ellen DeGeneres show namely agreement, assistance, clarification, disagreement, floor-taking, and tangentialization.